2020
DOI: 10.1590/0037-8682-0397-2020
|View full text |Cite
|
Sign up to set email alerts
|

High plasmid variability, and the presence of IncFIB, IncQ, IncA/C, IncHI1B, and IncL/M in clinical isolates of Klebsiella pneumoniae with bla KPC and bla NDM from patients at a public hospital in Brazil.

Abstract: Introduction: Antibiotic resistance in carbapenemase-producing Klebsiella pneumoniae is acquired and disseminated mainly by plasmids. Therefore, we aimed to investigate the occurrence of carbapenemase genes, analyze the genetic diversity by ERIC-PCR, and examine the most common plasmid incompatibility groups (Incs) in clinical isolates of K. pneumoniae from colonization and infection in patients from a hospital in Brazil. Methods: Twenty-seven isolates of carbapenem-resistant K. pneumoniae were selected and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
15
0
2
Order By: Relevance
“…In Brazil, KPC-2 is the most common CPase, carried on plasmids among K. pneumoniae belonging to different international lineages (e.g., sequence type (ST)258, ST101, and ST15) 64 . Clonal spread in Brazil 65,66 and certain South American countries has been extensive 64,67 . Reyes et al reviewed publications (in English or Spanish) until 2019; data from seven South American countries noted that K. pneumoniae belonging to clonal complex 258 was most common; the most prevalent CPase genes were KPC and NDM 68 .…”
Section: Carbapenemases (Cpases) and International Spreadmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, KPC-2 is the most common CPase, carried on plasmids among K. pneumoniae belonging to different international lineages (e.g., sequence type (ST)258, ST101, and ST15) 64 . Clonal spread in Brazil 65,66 and certain South American countries has been extensive 64,67 . Reyes et al reviewed publications (in English or Spanish) until 2019; data from seven South American countries noted that K. pneumoniae belonging to clonal complex 258 was most common; the most prevalent CPase genes were KPC and NDM 68 .…”
Section: Carbapenemases (Cpases) and International Spreadmentioning
confidence: 99%
“…Reyes et al reviewed publications (in English or Spanish) until 2019; data from seven South American countries noted that K. pneumoniae belonging to clonal complex 258 was most common; the most prevalent CPase genes were KPC and NDM 68 . A recent study in a hospital in Brazil reported 27 isolates of CP-resistant K. pneumoniae (CR-Kp); 24 (88.8%) produced KPC; 16 (59.2%) produced NDM; 13 (48.1%) expressed both genes 65 . In Venezuela, 19 isolates of CRKP co-expressing KPC-2 and VIM-2 were reported in a pediatric hospital in 2014 69 .…”
Section: Carbapenemases (Cpases) and International Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…IncFIB plasmid was present in 36 of 37 of the bacterial isolates. This conjugative plasmid has been associated with the dissemination of the bla NDM–1 , bla SHV–12 , bla CTXM–15 , and bla OXA–1 genes in K. pneumoniae ( Oliveira et al, 2020 ). Methods of circularization and annotation of the plasmid DNA using sequencing techniques that generate long-read sequences will offer insights into the content of those plasmids and its evolution and spread ( Ramsamy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the bla OXA-48 gene has been reported to be specifically encoded on the IncL sequence [ 10 , 20 ]. Although IncL/M plasmids are predominantly prevalent in the Mediterranean region and Western Europe [ 21 ], their global spread has been confirmed by identifications even in tropical Brazil [ 22 ]. Moreover, IncN-plasmids have also been described to be widely distributed in K. pneumoniae [ 16 , 23 , 24 ] and to harbor resistance genes, such as bla CTX-M-1 [ 25 ], bla KPC [ 26 ] and bla IMP-6 [ 27 ], respectively.…”
Section: Introductionmentioning
confidence: 99%